PENDEKATAN KEPEMIMPINAN DALAM MENINGKATKAN MORAL SANTRI DI PESANTREN - Nur Rahmadhani Sholehah SN; Suwadi (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2024)
The leadership approach in Islamic boarding schools has been an interesting study as Islamic boarding school leadership has differences from the leadership of other educational institutions. Islamic boarding school leadership, which is based on uswatun hasanah, is expected to be able to improve the morality of students (santri). The aim of this research is to examine leadership approaches, student morality in Islamic boarding schools, and improving the moral and ethics of students in Islamic boarding schools through leadership approaches. This type of research uses qualitative research. This research is library research. This research used an inductive approach that originates from the facts found then questions arise and relates them to existing theoretical studies and finally draws conclusions. Data analysis used the Miles and Huberman method, namely data reduction, data presentation, verification. The research results show that leadership approaches include the trait approach, behavioral approach, and situational approach. Santri morals include respecting teachers, etiquette in the books studied, covering one's private parts, ethics in speaking. Meanwhile, increasing the morality of students in Islamic boarding schools through a leadership approach includes providing learning, setting good examples, being responsible and collaborating. Keywords: Leadership Approach; Morals; Santri; Islamic Boarding School.   Abstrak Pendekatan kepemimpinan di pesantren memiliki kajian yang menarik karena kepemimpinan pesantren memiliki distingsi dengan kepemimpinan lembaga pendidikan yang lain. Kepemimpinan pesantren yang didasari oleh uswatun hasanah, diharapkan mampu meningkatkan moral peserta didik (santri). Tujuan penelitian ini adalah mengkaji tentang pendekatan kepemimpinan, moral santri di Pesantren, dan peningkatan moral santri di pesantren melalui pendekatan kepemimpinan. Jenis penelitian ini menggunakan penelitian kualitatif. Penelitian ini merupakan penelitian library research (penelitian kepustakaan). Pendekatannya ialah pendekatan induktif berasal dari fakta yang ditemui kemudian timbul pertanyaan dan mengaitkannya dengan kajian-kajian teori yang ada lalu mengambil kesimpulan. Analisis data dengan metode Miles dan Huberman yaitu reduksi data, penyajian data, verifikasi. Hasil penelitian menunjukan bahwa pendekatan kepemimpinan diantaranya pendekatan sifat, pendekatan perilaku, dan pendekatan situasional. Moral santri diantaranya meliputi memuliakan guru, adab dalam kitab yang dipelajari, menutup aurat, etika dalam berbicara. Sedangkan peningkatan moral santri di pesantren melalui pendekatan kepemimpinan diantaranya dilakukan dengan pemberian pembelajaran, memberikan teladan yang baik, bertanggungjawab dan kolaborasi. Kata Kunci: Pendekatan Kepemimpinan; Moral; Santri; Pesantren.